Kepatuhan Wajib Pajak UMKM: Peran Sosialisasi Perpajakan, Pemahaman Perpajakan, dan Kepercayaan Publik kepada Pemerintah - Wardani, Putri Puspita; Sari, Ika (Gorontalo Accounting Journal, 2025)
This study aims to determine the effect of tax socialization, tax understanding, and public trust in the government on taxpayer compliance. This research is a causal study. The population in this study consists of all MSME taxpayers in the Ciputat District, with a sample of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using descriptive statistical analysis, hypothesis testing, as well as outer and inner model testing with Smart Partial Least Square (SmartPLS) 4.0 software. The results show that tax socialization has a positive and significant effect on MSME taxpayer compliance, tax understanding has a positive and significant effect on MSME taxpayer compliance, and public trust in the government has a positive and significant effect on MSME taxpayer compliance.